2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2011
DOI: 10.1109/iembs.2011.6090582
|View full text |Cite
|
Sign up to set email alerts
|

Single-crystal cubic silicon carbide: An in vivo biocompatible semiconductor for brain machine interface devices

Abstract: Single crystal silicon carbide (SiC) is a wide band-gap semiconductor which has shown both bio- and hemo-compatibility [1-5]. Although single crystalline SiC has appealing bio-sensing potential, the material has not been extensively characterized. Cubic silicon carbide (3C-SiC) has superior in vitro biocompatibility compared to its hexagonal counterparts [3, 5]. Brain machine interface (BMI) systems using implantable neuronal prosthetics offer the possibility of bi-directional signaling, which allow sensory fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…14,15 It has been also confirmed that SiC with 800-1000 mm pore size had good osteogenic and osteoconductive properties, and its promotion of adhesion, proliferation, and differentiation of primary culture osteoblasts in our previous research. [24][25][26] We used the same materials without simulating the natural bone.…”
Section: Discussionsupporting
confidence: 53%
“…14,15 It has been also confirmed that SiC with 800-1000 mm pore size had good osteogenic and osteoconductive properties, and its promotion of adhesion, proliferation, and differentiation of primary culture osteoblasts in our previous research. [24][25][26] We used the same materials without simulating the natural bone.…”
Section: Discussionsupporting
confidence: 53%
“…The material also is a semiconductor, and as such can be fabricated into electrical devices which can be used for sensing or signal reception and transmission. We have shown that the crystalline form of this material does not cause cytotoxic response in vitro and has not initiated chronic inflammatory response within animal models in vivo [41,44,57,128,155]. We have shown that it is a promising material to solve the longevity and reliability issues plaguing both continuous glucose monitors as well as neural implants [41,44,128,155].…”
Section: Sic Biomedical Perspectivesmentioning
confidence: 92%
“…Finally, it should be mentioned that graphene can be grown also on the cubic SiC polytype (3C-SiC), and in particular large area (more than hundreds of square microns) and highly [120] crystalline graphene can be obtained in the (111) orientation of this crystal which naturally accommodate the six-fold symmetry of graphene [125]. Cubic SiC possesses physicochemical properties which make it attractive for use in implantable devices [41]. Moreover, as it can be heteroepitaxially grown on Si it allows for an easy integration with Si electronics while providing a higher degree of biocompatibility than Si.…”
Section: Graphene On Sic In Vitromentioning
confidence: 99%
See 2 more Smart Citations